Indonesia's Role in Fulfilling the Right to Education Elementary and Intermediate in Border Areas - Itasari, Endah Rantau; Mangku, Dewa Gede Sudika; Yuliartini, Ni Putu Rai; Purwendah, Elly Kristiani; Yustitianingtyas, Levina; Harjiyatni, Francisca Romana; Wirawan, I Gusti Made Arya Suta (International Journal of Criminology and Sociology, 2021)
The role of the state in carrying out educational development and in order to fulfill the right to education, especially primary and secondary education in border areas must be further enhanced. The state must be present among school-age children in border areas by manifesting itself in the form of appropriate and representative school buildings. The state must exist in the form of adequate educational support facilities. The state must be present in the form of teachers and education personnel who are sufficient in number and have competence. The state must be present in the form of budget politics that supports education development in border areas. The state must also be present in a curriculum that suits the needs of school-age children in border areas as well as enhances their national insight.